Psychosocial status and prenatal care of unintended pregnancies among low-income women - Alanna M. Cruz-Bendezú; Grace V. Lovell; Brianna Roche; Meghan Perkins; Tiffany L. Blake-Lamb; Elsie M. Taveras; Meg Simione (BMC, 2020)
Abstract Background Nearly half of all pregnancies in the United States are reported as unintended and rates are highest among women of low socioeconomic status. The purpose of this study was to examine the associations between unintended pregnancies and maternal mental health and timing of prenatal care among low-income women. Methods In this cross-sectional study, 870 women, whom were participating in the First 1000 Days program in three community health centers in the Boston area, were enrolled at their first prenatal visit from August 2016 - September 2017. We assessed pregnancy intention by self-report using the Pregnancy Risk Assessment Monitoring System. We used self-reported survey information and electronic health record data to assess the following outcomes: current stress, current depression, and timing of initial prenatal visit. We used multivariable logistic regression models to examine associations and adjusted for sociodemographic factors. Results Women were a mean (SD) age of 29.3 (6.1), and 39.2% reported that their pregnancy was unintended. 50.6% of women were Hispanic, 28.4% were White, 10.1% were Black, and 10.9% were other races. 78.9% of women reported an annual household income <$50,000. Overall, 26.7% of women reported current stress, 8.2% reported current depression, and 18.3% of women initiated prenatal care after their first trimester. In multivariable analyses, women with unintended pregnancies had higher odds of experiencing current stress (OR: 1.72; 95% CI: 1.22, 2.41), current depression (OR: 1.83; 95% CI: 1.04, 3.20), and initiation of prenatal care post-first trimester (OR: 1.84; 95% CI: 1.23, 2.74). Conclusions Unintended pregnancies were associated with current stress and depression, and delayed prenatal care in this sample of low-income women suggesting the importance of identifying high-risk women and tailoring interventions to support women's needs. Trial registration ClinicalTrials.gov (NCT03191591; Retrospectively registered on June 19, 2017).